A10: Younger Age and Severity of Renal Presentation Distinguishes Microscopic Polyangiitis From Granulomatosis With Polyangiitis in Children: An ARChiVe Study. Issue 11 (March 2014) - Bingham, Debra; Muscal, Eyal; Nanda, Kabita; Wahezi, Dawn M.; Spalding, Steven J.; Twilt, Marinka; Benseler, Susa; Cabral, David A.
Abstract : Background/Purpose: Comparisons of pediatric ANCA‐associated vasculitis subtypes (AAV) are limited by the paucity of reported cases, standardized definitions, and overlapping classification criteria. Published work from ARChiVe (A Registry for Childhood Vasculitis) demonstrated modifications of validated classification algorithms applied to pediatric patients with AAV can classify each patient to mutually exclusive diagnostic categories. We compared presenting features of children with microscopic polyangiitis (MPA) and granulomatosis with polyangiitis (GPA) classified according to this methodology. Methods: A pediatric modification of the European Medicines Agency (EMA) algorithm for classifying AAV and polyarteritis nodosa (incorporating the EULAR/PRINTO/PRES pediatric classification criteria for GPA) was applied to patients in ARChiVe censored to April 2012. We compared characteristics of patients classified as having MPA and GPA. STATA (Statcorp, 2013) was used to calculate frequencies, percentages, and chi‐squared with fisher's exact for categorical variables and means, standard deviations, and t‐tests for continuous variables. Results: One hundred fifty‐two of 227 children in ARChiVe met criteria for diagnosis of MPA (n = 22) or GPA (n = 130). Characteristics and presenting features are shown in Table 1 . Children with MPA were younger at diagnosis (mean diff. 2.7y, p = <0.01). Renal involvement was predominant in both groups. Renal biopsies in 40% of both groups were consistent with pauci‐immune, necrotizing glomerulonephritis. Children with MPA had higher rates of nephrosis, renal failure requiring dialysis, and abnormal creatinine clearance (Table 1 ). Upper and lower airway involvement was more prevalent among those with GPA largely in accordance with surrogate GPA features used to differentiate GPA and MPA in the EMA algorithm. The majority of patients presented with constitutional symptoms, however, other organ systems were less frequently involved. Most patients received combination therapy corticosteroids and cytoxan (64% MPA, 81% GPA) with additional plasmapheresis (29% MPA, 21% GPA), rituximab (14% MPA, 3% GPA) or methotrexate (7% MPA, 1% GPA). The remainder of children received combination corticosteroids and methotrexate or rituximab, without cytoxan (12% MPA, 11% GPA). A larger proportion of patients with MPA received antihypertensive agents and/or ACE inhibitors (64% vs 35%, p = 0.01). Conclusion: Children with AAV had predominantly renal and constitutional manifestations. Younger age and a more severe renal disease phenotype may characterize MPA with patients requiring additional treatment for the consequences of kidney disease. The wide variations in time to diagnosis continue to suggest that pediatric AAV is poorly recognized. Ongoing biomarker‐driven studies may complement systems for subclassifying patients with AAV.